2016
DOI: 10.1172/jci.insight.88034
|View full text |Cite
|
Sign up to set email alerts
|

Glymphatic fluid transport controls paravascular clearance of AAV vectors from the brain

Abstract: Adeno-associated viruses (AAV) are currently being evaluated in clinical trials for gene therapy of CNS disorders. However, host factors that influence the spread, clearance, and transduction efficiency of AAV vectors in the brain are not well understood. Recent studies have demonstrated that fluid flow mediated by aquaporin-4 (AQP4) channels located on astroglial end feet is essential for exchange of solutes between interstitial and cerebrospinal fluid. This phenomenon, which is essential for interstitial cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…(20, 101). A separate study showed similar results, observing reduced clearance of an adeno-associated viral-9 (AAV9) vector in a different strain of Aqp4 −/− mice(103). Aβ clearance was also reduced ~55% in Aqp4 −/− mice, suggesting that glymphatics are responsible for about half of the clearance of soluble Aβ in the brain(20).…”
Section: Glymphatic Systemmentioning
confidence: 67%
“…(20, 101). A separate study showed similar results, observing reduced clearance of an adeno-associated viral-9 (AAV9) vector in a different strain of Aqp4 −/− mice(103). Aβ clearance was also reduced ~55% in Aqp4 −/− mice, suggesting that glymphatics are responsible for about half of the clearance of soluble Aβ in the brain(20).…”
Section: Glymphatic Systemmentioning
confidence: 67%
“…Follow-up of that finding by the NMU group showed that Aβ accumulation and cerebral amyloid angiopathy were significantly increased in a double-hit murine model with Aqp4 deletion and Aβ over-expression (8). The URMC/OHSU groups subsequently reported that deletion of Aqp4 aggravated neurofibrillary pathology following TBI (6), whereas the UNC group showed that deletion of Aqp4 significantly reduced clearance of AAV (11). Thus, these reports conceptually address the same idea, although the replications entailed different approaches and methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…Lundgaard et al, (2016) reported that glymphatic clearance of lactate was reduced in Aqp4 KO mice (10). Finally, Murlidharan et al (2016) showed that Aqp4 KO mice exhibit significantly impaired clearance of adeno-associated viruses (AAV) infused into the ventricles, and concluded that glymphatic transport profoundly affects various aspects of AAV gene transfer in the CNS (11).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, they used AQP4 −/− mice, which are global APQ4 gene knockouts signifying that AQP4 channels are absent everywhere; and showed that glymphatic clearance was significantly reduced compared with normal littermates. The importance of AQP4 −/− channels in facilitating efficient glymphatic transport and clearance was recently supported by evidence of parenchymal retention of adeno-associated viruses in aging mice which coincided with loss of AQP4 channel polarization on glial cell end-feet (Murlidharan and others 2016). Collectively these experiments led to the conceptualization of the “glymphatic” pathway as a macroscopic system for waste clearance comprising a network of peri-arterial and peri-venous conduits coupled by AQP4 water channels on glial cells’ end-feet (Fig.…”
Section: Conceptualization Of the Glymphatic Pathwaymentioning
confidence: 96%